Time-reversibility of SARS-CoV-2 infection on basic semen parameters - Chun-Ling Liu; Kai Fu; Fang Lü; Ming-Wei Chen; Hong Zhang; Jin-Chun Lu (Journal of Men's Health, 2024)
SARS-CoV-2 infection may affect semen quality. However, there is limited evidence on whether this effect is reversible. Retrospective analysis was done on the same male patient’s semen quality prior to SARS-CoV-2 infection, less than 74 days following recovery from SARS-CoV-2 infection, and more than 74 days following recovery in order to confirm. Consequently, the sperm concentration (44.10 (28.00, 75.20) vs. 66.00 (47.05, 135.30) × 106/mL, p < 0.001), sperm motility ((43.22 ± 21.34)% vs. (51.65 ± 15.41)%, p = 0.0105), percentage of progressively motile sperm (PR) ((39.76 ± 20.58)% vs. (46.88 ± 15.26)%, p = 0.0243) and percentage of normal morphological sperm ((2.70 ± 1.82)% vs. (3.58 ± 2.00)%, p = 0.0299) of 45 male patients 30 to 71 days after recovery from SARS-CoV-2 infection were significantly lower than those before SARS-CoV-2 infection, while there was no significant difference in semen volume (3.20 (2.10, 4.65) mL vs. 3.20 (2.45, 4.55) mL, p = 0.4819) between them. The sperm concentration, motility and PR of 8 patients 77 to 125 days after recovery from SARS-CoV-2 infection (68.75 (31.50, 114.1) × 106/mL, (44.23 ± 25.73)% and (39.76 ± 25.23)%) were higher than those 30 to 71 days after recovery from SARS-CoV-2 infection (20.05 (13.58, 30.10) × 106/mL, (30.11 ± 22.05)% and (26.56 ± 21.55)%), and there were no significant differences from those before SARS-CoV-2 infection (50.05 (41.03, 90.35) × 106/mL, p = 0.8438; (50.24 ± 13.62)%, p = 0.5126; and (45.76 ± 12.97)%, p = 0.5251). In conclusion, SARS-CoV-2 infection may affect one spermatogenesis cycle of a male patient for about 74 days, and the patient may return to the normal state in the next spermatogenesis cycle.